93.8k views
14 votes
Factor -45x^3-60x^2-20x

2 Answers

3 votes

Answer:

−5x(3x+2)^2

Explanation:

-45x^3-60x^2-20x

Factor out 5.

5(−9x^3-12x^2-4x)

Consider −9x^3-12x^2-4x. Factor out x.

x(−9x^2−12x−4)

Consider −9x^2−12x−4 Factor the expression by grouping. First, the expression needs to be rewritten as −9x^2+ax+bx−4. To find a and b, set up a system to be solved.

a+b=−12

ab=−9(−4)=36

Since ab is positive, a and b have the same sign. Since a+b is negative, a and b are both negative. List all such integer pairs that give product 36.

−1,−36

−2,−18

−3,−12

−4,−9

−6,−6

Calculate the sum for each pair.

−1−36=−37

−2−18=−20

−3−12=−15

−4−9=−13

−6−6=−12

The solution is the pair that gives sum −12.

a=−6

b=−6

Rewrite −9x^2−12x−4 as (−9x^2−6x)+(−6x−4).

(−9x^2−6x)+(−6x−4)

Factor out −3x in the first and −2 in the second group.

−3x(3x+2)−2(3x+2)

Factor out the common term 3x+2 by using distributive property.

(3x+2)(−3x−2)

Rewrite the complete factored expression.

5x(3x+2)(−3x−2)

User Eightgate
by
4.7k points
6 votes

Answer:

  • -5x(3x+2)²

Explanation:

Factoring the given expression:

  • -45x³ - 60x² - 20x =
  • -5x(9x² + 12x + 4) =
  • -5x(9x² + 6x + 6x + 4) =
  • -5x(3x(3x + 2) + 2(3x + 2))
  • -5x(3x + 2)(3x + 2)
  • or
  • -5x(3x+2)²
User SlashJ
by
4.8k points